Incremental Value of Three‐Dimensional Transesophageal Echocardiography over the Two‐Dimensional Technique in Percutaneous Closure of Aortic Paraprosthetic Regurgitation. Issue 9 (October 2014) - Alli, Oluseun O.; Hsiung, Ming C.; Guvenc, Tolga; Neill, John; Elguindy, Mostafa; Ahmed, Mustafa I.; Gaba, Saurabh; Nanda, Navin C.
<x xml:space="preserve">Abstract</x> We describe 2 patients with significant aortic paraprosthetic regurgitation who underwent percutaneous closure where live/real time three‐dimensional transesophageal echocardiography provided incremental value over two‐dimensional transesophageal echocardiography.